2019
DOI: 10.3390/nu11122875
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Quercetin in Hepatocarcinoma In Vitro and In Vivo Models: A Systematic Review

Abstract: Quercetin is a flavonoid present in fruits, vegetables and plants with antioxidant, anti-inflammatory and anticancer properties. Its beneficial activities have been demonstrated in different human pathologies, including hepatoprotective effects against liver disorders. High mortality and late diagnosis of the primary liver tumor hepatocarcinoma (HCC) makes this cancer an interesting target for the study of quercetin effects. Our aim was to systematically review antitumor activities of quercetin in HCC preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 80 publications
(276 reference statements)
3
45
0
Order By: Relevance
“…Carcinogenetic processes often involve oxidative stress, and administration of antioxidant molecules may reduce the damage to cancerous hepatocytes [ 61 , 62 , 63 ]. Melatonin acts as an indirect antioxidant and as a direct free radical scavenger and displays an important role as an immunomodulatory and chronobiotic agent in different tissues, including liver [ 6 , 14 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carcinogenetic processes often involve oxidative stress, and administration of antioxidant molecules may reduce the damage to cancerous hepatocytes [ 61 , 62 , 63 ]. Melatonin acts as an indirect antioxidant and as a direct free radical scavenger and displays an important role as an immunomodulatory and chronobiotic agent in different tissues, including liver [ 6 , 14 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been an increasing interest on the use of flavonoids as anticancer agents [ 62 ]. In vitro experiments have also demonstrated that 2 and 4 mM melatonin co-administration potentiates the proapoptotic effects of EGCG in HepG2 cells by inhibition of Bcl-2 and COX-2, resulting in an enhanced cytotoxicity against HCC cells [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin is an excellent free radical scavenging antioxidant [344] and is considered one of the most effective antioxidants [351]. Consequently, quercetin exhibits promising effects against cancer [339,352] in vitro and in vivo [353][354][355][356][357][358][359][360]. Nevertheless, its potential impacts in clinical applications are drastically limited due to its poor solubility, low bioavailability, and instability [361].…”
Section: Quercetinmentioning
confidence: 99%
“…Notably, it was reported that a low concentration of quercetin acted as an antioxidant, but high-dose quercetin induced oxidative stress against cancer cells, thus displaying anticancer effects [ 113 ]. Recent reports have shown that quercetin is excellent in combating ovarian cancer [ 114 ] and hepatocarcinoma [ 115 ]. In addition, quercetin inhibited the overgrowth of human gastric cancer cells (in the presence of 53 µM quercetin) [ 116 ], MDA-MB-453 (in the presence of 100 µM quercetin) [ 117 ], and MCF-7 (in the presence of 150 µM quercetin) [ 118 ] via the induction of intrinsic and extrinsic apoptosis pathways and cell cycle arrest.…”
Section: Anticancer Effects Of Two Representative Flavonoids From mentioning
confidence: 99%